Menciptakan Kepuasan Dan Keputusan Nasabah Melalui Inovasi Kualitas Layanan Sdm Dan Strategi Pemasaran Pada PT Bank NTB Syariah KCP Kempo Kabupaten Dompu - Abdillah, Junaedi; Taryono, Taryono; Cita, Fitriah Permata (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Customer satisfaction and decisions are closely related to marketing strategy and service quality. The better a marketing strategy and service quality, the higher the customer's interest in a bank. The opposite is also true. This fact is what the researchers found at Bank NTB Syariah KCP Kempo, Dompu Regency. There fore a study was conducted to investigate this situation. This research as mentioned above was conducted at Bank NTB Syariah KCP Kempo, Dompu Regency. While the object of research is the customer of the Bank starting in September 2021 until October 2021. The Bank NTB Syariah Kempo Sub-Branch Office is located at Jalan Soro Kempo with a population of 500 customers and a sample of 83 customers. This type of research is quantitative descriptive and technical data analysis using regression analysis and hypotheses with a series of tests, namely validity test, reliability test, deviation test, classical assumption, and multiple linear regression analysis test.